Evaluation and comparison of anti-Candida effect of heat cure polymethylmethacrylate resin enforced with silver nanoparticles and conventional heat cure resins: An in vitro study - S Suganya; S C Ahila; B Muthu Kumar; M Vasantha Kumar (Wolters Kluwer Medknow Publications, 2014)
Recent years have been dominated by research in nano science. Dentistry is no exception and there is increased research on nanoparticles in dentistry. Complete dentures increase the carriage of Candida in healthy patients, and the proliferation of C. albicans can be associated with denture-induced stomatitis. Purpose: To evaluate the anti-Candida effect of heat cure denture base resins reinforced with Ag° in the ratio of 4:1, 3:1, 2:1 (Groups B, C, and D, respectively) to the weight of denture base resins. Materials and Methods: Ag° were synthesized by chemical reduction method, incorporated into the polymer powder according to the ratio for each group, subjected to polymerization and microbial assay was calculated for the reference C. albicans strains by agar diffusion method for the incubation period of 24 h. Results: Group D showed multifold decrease in the colony-forming units. Conclusion: The antimicrobial effect of silver could be used vividly in the denture base for immunocompromised and geriatric patients.